The Analysis of Vocational Nurses' Perceptions of the Suitability of Graduate Competencies with the World of Work in Jambi City in 2022 - Aguspairi; Marinawati Ginting; Sondang Silitonga; Ismail Usman (Poltanesa, 2022)
This study aims to look at the description of vocational nurses' perceptions of the competencies obtained during their education on campus with those faced in the world of work after working, especially in hospitals. So far, nursing vocational higher education in Indonesia in the learning process has implemented the concept of link and match, this is in line with current government policy, the government gives full attention to vocational education. The design used in this study is a survey method using online questionnaire filling techniques using google form. The results showed that most respondents stated that their competence was appropriate or aligned between the knowledge gained while on campus and when working in the hospital. so far, the nursing vocational higher education curriculum applies the concept of link and match in the learning process. In the learning process, students obtain various forms of learning experiences, including learning experiences in the classroom, laboratory, clinical and field vehicles, and are equipped with learning facilities and infrastructure that are in accordance with standards and a high percentage of semester credit for laboratory, clinical and field practicum.